Efek Ramuan Tradisional Kaliputih terhadap Kadar Glukosa Darah Puasa, SOD, HbA1c, dan Histopatologi Pankreas pada Tikus Diabetes yang Diinduksi Streptozotocin) - Kusumo, Djati Wulan; Efendi, Yuli Nurullaili; Kintoko, Kintoko; Yuliana, Tri Puspita; Waznah, Urmatul; Muldiyana, Tya; Pulhehe, Hasni (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Prevention of DM by controlling sugar and lipid levels is the main therapy. The traditional medicine diabetes herb from Kaliputih Batur, Banjarnegara, Central Java consists of 11 kinds of medicinal plants that are empirically proven to be efficacious for diabetes mellitus. The potion is prepared by the infundation method. Three control groups (normal, positive, and negative) and three test groups with different doses (18, 36, and 54 mL/kg BW) that had previously been induced by streptozotocin were created using Sprague Dawley (SD) albino rats. Using HE staining, observations were obtained on fasting blood glucose (FBG), superoxide dismutase (SOD), HbA1c, and pancreatic organs. At doses of 36 and 54 mL/kg bw, results analysis of biochemical parameters of FBG levels revealed a substantial decline (P<0.05). At all dosages of the herb, there was a significant change in SOD activity (P<0.05), and at a dose of 18 mL/kg BW compared to negative control, there was a significant difference in HbA1c levels (P<0.05). HE staining results revealed no distinctpathological alterations in pancreatic organ at the test dose compared to negative control with necrosis in the Langerhans insula. Herbal medicine for diabetes traditional medicine from Kaliputih Batur, Banjarnegara, Central Java has decreased blood glucose.